HAK BURUH UMKM PEREMPUAN BERDASARKAN UNDANG-UNDANG CIPTA KERJA DI KABUPATEN PINRANG - Amin, Astrid Amanda Putri; Hasan, Hamzah; Larissa, Dea (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
The existence of female workers in the MSME industry is a form of empowering women in the world of work but does not rule out the possibility of discrimination in the work environment. This study aims to determine the implementation of women's MSME labor rights based on Law Number 11 of 2020 concerning Job Creation in Pinrang Regency. The type of research conducted is field qualitative research with juridical approaches. The results of the study show that female MSME workers in Pinrang Regency have obtained their rights in accordance with statutory provisions, and the government has monitored every business actor, to minimize the gap between women workers.